2016
DOI: 10.1017/s0007114515005292
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of serum 25-hydroxyvitamin D concentration in Finnish children: the Physical Activity and Nutrition in Children (PANIC) study

Abstract: We studied vitamin D intake, serum 25-hydroxyvitamin D (S-25(OH)D) concentration, determinants of S-25(OH)D and risk factors for S-25(OH)D <50 nmol/l in a population sample of Finnish children. We studied 184 girls and 190 boys aged 6-8 years, analysed S-25(OH)D by chemiluminescence immunoassay and assessed diet quality using 4-d food records and other lifestyle factors by questionnaires. We analysed the determinants of S-25(OH)D using linear regression and risk factors for S-25(OH)D <50 nmol/l using logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
49
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 43 publications
9
49
1
1
Order By: Relevance
“…In line with our findings, two recent Finnish studies showed increased 25(OH)D concentrations among 2- to 12-year-olds in 2003–2006 and 6- to 8-year-olds in 2007–2009 after the fortification of milk products with vitamin D began in 2003 [15, 16]. In their study, Mäkinen et al [15] reported that the frequency of vitamin D insufficiency in Finnish children almost halved from 69.9% in 1998–2002 to 37.3% in 2003–2006.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with our findings, two recent Finnish studies showed increased 25(OH)D concentrations among 2- to 12-year-olds in 2003–2006 and 6- to 8-year-olds in 2007–2009 after the fortification of milk products with vitamin D began in 2003 [15, 16]. In their study, Mäkinen et al [15] reported that the frequency of vitamin D insufficiency in Finnish children almost halved from 69.9% in 1998–2002 to 37.3% in 2003–2006.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the majority of the children with milk allergy took vitamin D supplements, and the frequency of their fish consumption did not differ from that of the other children, but still their 25(OH)D levels were significantly lower. Our finding is similar to that of a recent study on 6- to 8-year-old Finnish children, where the strongest determinant of vitamin D status was consumption of milk, and it implies that vitamin D obtained from fortified dairy products is an effective means of improving the vitamin D status [16]. Those children who do not regularly consume fortified milk products are at risk of a lower vitamin D status and might benefit from higher vitamin D supplementation.…”
Section: Discussionsupporting
confidence: 89%
“…It was found that the mean value of vitamin D intake in this study was slightly higher compared to the EsKiMo study, where the intake was 2.55 µg/day in males and 2.50 µg/day in females, but was lower compared to an earlier study on Finnish girls [57], where their intake was 4.3 µg/day. A recent study found that the mean vitamin D intake from both food and supplements for Finnish children was 5.9 µg/day in males and 7.7 µg/day in females [58]. Even though female adolescents have higher BMC value compared to male adolescents, it has been found that the male adolescents have a normal mean BMC level but with a tendency for higher vitamin D intake and higher physical activity levels ( p = 0.001) compared to females.…”
Section: Discussionmentioning
confidence: 99%
“…One study performed seasonal supplementation of 13,700 IU over seven days (TABLE 1). None of the studies reported side effects during supplementation (19)(20)(21)(22)(23)(24) . (24) 159 Canadian children of both sexes.…”
Section: Figure 2 Prevalence Of Vitamin D Deficiency Between Articlementioning
confidence: 99%
“…The reviewed articles differ in some respects such as the serum 25(OH)D values considered to be deficient, insufficient or adequate. Three of the six articles considered deficiency as levels below 20 ng/ mL (19)(20)(21) , one considered it as below 18 ng/mL (22) , another below 15 ng/mL (23) , and the latter below 11 ng/mL (24) . Therefore, half of the studies analyzed considered deficiency as below 20 ng/mL.…”
Section: Figure 1 Flowchart Review Of the Findings In The Databasementioning
confidence: 99%